PENETAPAN KADAR FLAVONOID DAN TANIN EKSTRAK ETANOL DAUN NANGKA (Artocarpus heterophyllus Lam.) DENGAN SPEKTROFOTOMETRI UV-VIS - Wahyuni, Sri; Simanjuntak, Helen Anjelina; Purba, Hermawan; Ginting, Junius Gian (LPPM Universitas Bakti Tunas Husada, 2024)
Jackfruit (Artocarpus heterophyllus Lam.) belongs to the moraceae family. Traditionally, jackfruit is used to treat fever, convulsions, asthma, diarrhea, anemia, cough and inflammation. The presence of flavonoid and tannin compounds isolated from jackfruit leaves has pharmacological activity in health. The purpose of this study was to screen the phytochemicals of secondary metabolites of flavonoids and tannins, and to determine the levels of secondary metabolites of flavonoids and tannins in jackfruit leaves using uv-vis spectrophotometry. The stages of this study began with sample collection, extraction, phytochemical screening, and testing of flavonoid and tannin levels. The results of phytochemical screening showed the presence of alkaloids, flavonoids, tannins, saponins, and steroids/triterpenoids in the crude drug and jackfruit leaf extract. The total flavonoid content was 234.9 mgQE/g with an R2 value of 0.9916, and for measuring the total tannin content was 343.3 mgTAE/g with an R2 value of 0.9956. The conclusion of this study is that the ethanol extract of jackfruit leaves contains flavonoid and tannin compounds with a total flavonoid content of 234.9 mgQE/g and a total tannin content of 343.3 mgTAE/g.